Antibacterial and antioxidant properties of red mold rice fermented by different Monascus purpureus strains with varying citrinin production in glycine-supplemented rice media - Ristiarini, Susana; Nugerahani, Ira; Kuswardani, Indah; Srianta, Ignatius (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Red mold rice (RMR), a fermented product from Monascus purpureus, is traditionally used as a natural dye and flavor enhancer. The fermentation process produces various secondary metabolites, including pigments with antioxidant properties and citrinin with antibacterial properties. Adding glycine to the fermentation media lowers citrinin levels while enhancing red pigment content, potentially impacting the antibacterial and antioxidant activities of RMR. This study aimed to evaluate the antibacterial and antioxidant properties and quantify pigments in RMR extracts from different M. purpureus strains with varied citrinin production in glycine-supplemented rice media (GSRMR). A Non-Factorial Randomized Block Design was utilized, with isolates classified as low citrinin (JK2 and JK9B) and high citrinin (JK9A). Results revealed distinct metabolic profiles among strains (i.e., JK2, JK9A, JK9B) grown in GSRMR, affecting yield, pigment content, color value, and citrinin content. Notably, the JK2 extract demonstrated a larger inhibition zone against S. aureus, indicating superior antibacterial activity, while JK9B exhibited enhanced DPPH radical scavenging, FRAP, and TAC, underscoring its superior antioxidant properties. Furthermore, antibacterial and antioxidant properties in GSRMR were not related to the pigments and citrinin contents.